Importance of Sugarcane in Brazilian and World Bioeconomy - Heinrichs, Reges [UNESP]; Otto, Rafael; Magalhães, Aline [UNESP]; Meirelles, Guilherme Constantino [UNESP] (Springer Nature, 2017)
The area of sugarcane (Saccharum spp.) cultivation totaled 27 million hectares in the world and 10 million hectares in Brazil. Sugarcane is a valuable crop considering the potential to produce sugar, ethanol, biodegradable products, energy generation and food for animal production. In tropical conditions, high biomass production in the range of 150–300 Mg ha–1 year–1 can be achieved, depending on the management and production system employed. Due to great adaptation to different types of soil and environment, sugarcane could be produced in over 100 countries to supply biofuel and food to the world. Improvement in the production process adopted in Brazil in the last decade, including mechanical planting and harvesting, new methods of sugarcane planting, control of pests, diseases, nutrition and fertilization, has increased sugarcane yield in Brazil while improving work-conditions and social aspects of sugarcane cultivation. Therefore, the high potential production of sugarcane, its varied uses and its ability to be cultivated in regions with low economic and social development indicates that sugarcane cultivation could become a key source of income and improve life-quality in many regions. However, political and governmental organization is required to achieve this goal.